Pengaruh Kualitas Event Terhadap Minat Berkunjung Kembali Ke Event Sport Tourism Wsl Krui Pro 2024 - Vitha Octavanny; Bintang Al Aziz; Fahrurozy Darmawan (Politeknik Pariwisata NHI Bandung, 2026)
This study aims to identify the effect of event quality on the intention to revisit the Wsl Krui Pro 2024 sport tourism event. The method used is quantitative descriptive. The independent variables of this study are Access Quality, Accommodation Quality, Venue Quality, and Contest Quality. The dependent variable in this study is the intention to revisit. The sample obtained was 100 respondents. The hypothesis of this study was tested using IBM SPSS 23. The results of this study state that the average value of the Access Quality variable is that there are various transportation options to get to the sport venue (land, air, sea), Accomadation Quality the facilities provided by the accommodation are in accordance with the price paid, Venue Quality the facilities at the event venue are good and comfortable, Contest Quality the audience feels that the level of competition in this event is quite challenging and in accordance with the expectations of the audience and the variable of intention to revisit the results of the match is announced to the audience. There are two indicators, namely Access Quality and Accommodation Quality, which do not have a partial effect on the intention to revisit. While the other two indicators, namely Venue Quality and Contest Quality, have a partial impact on the intention to revisit. Then, in the Sport Tourism Event Quality variable, it was found that all indicators had a simultaneous effect on interest in revisiting. Keywords: Event Quality; Sport Tourism; Revisit Intention; WSL Krui Pro Abstrak Penelitian ini bertujuan untuk mengidentifikasi pengaruh kualitas event terhadap minat berkunjung kembali ke evet sport tourism WSL Krui Pro 2024. Metode yang digunakan adalah kuantitatif deskriptif. Variabel independen penelitian ini yaitu Access Quality, Accomodation Quality, Venue Quality, dan Contest Quality. Sedangkan variabel dependen penelitian ini yaitu minat berkunjung kembali. Sampel yang diperoleh berjumlah 100 responden. Hipotesis penelitian ini diuji menggunakan IBM SPSS 23. Hasil penelitian ini menyatakan bahwa nilai rata-rata tersebut pada variabel Acces Quality tersedia berbagai pilihan transportasi untuk menuju ke sport venue (darat, udara, laut), Accomadation Quality fasilitas yang diberikan oleh penginapan sesuai dengan harga yang dibayarkan, Venue Quality Fasilitas di veneu event baik dan nyaman, Contest Quality penonton merasa bahwa tingkat persaingan dalam acara ini cukup menantang dan sesuai dengan ekspektasi penonton dan variabel minat berkunjung kembali informasi hasil pertadingan diumumkan kepada penonton. Terdapat dua indikator yaitu Access Quality dan accomodation Quality yang tidak berpengaruh secara parsial terhadap minat berkunjung kembali. Sedangkan dua indikator lainnya yaitu Venue Quality dan Contest Quality berpengaruh secara parsial terhadap minat berkunjung kembali. Kemudian pada variabel Kualitas Event Sport Tourism, ditemukan bahwa keseluruhan indikator berpengaruh secara simultan terhadap minat berkunjung kembali. Kata Kunci: Kualitas Event; Sport Tourism; Minat Berkunjung Kembali; WSL Krui Pro